Dictyostelids from Jilin Province, China. I - Liu, Pu; Li, Yu (Phytotaxa, 2014)
Six species of dictyostelid cellular slime molds (dictyostelids) in two genera were isolated from soil samples collected from Jilin Province in China. Two of these species (Dictyostelium multistipes and D. gracile) are new to China, and D. clavatum is recorded for the first time in the northern part of the country, being known previously only from Taiwan. Descriptions and illustrations are provided for these species based on our collections.